Network technologies in the professional education and advanced training of engineers - A. N. Nikulin; I. V. Zakharova (Вестник университета)
The article substantiates the effectiveness of network training and e-learning technologies in the professional training and advanced training of engineering personnel at a technical university. The paper analyses e-learning technologies in the context of competence-based and activity-based approaches to the organization of the educational process. The study considers Universities as the core elements of the regional educational space, integrating and developing the potential of network interaction of its subjects. The authors propose the definition of the concept of “network educational space”. The article describes the experience of network training of personnel in the production sectors of the Ulyanovsk region in 2014-2020. Based on the analysis of the teaching practice of the Ulyanovsk State Technical University, the study proposes a model of the electronic information and educational environment of an educational organization. The authors formulate recommendations for the development of a network educational space in the region that meets the needs of the labor market.